2009
DOI: 10.1016/j.jacc.2009.07.022
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular Effect of Bans on Smoking in Public Places

Abstract: Smoking bans in public places and workplaces are significantly associated with a reduction in AMI incidence, particularly if enforced over several years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
201
2
27

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(241 citation statements)
references
References 41 publications
11
201
2
27
Order By: Relevance
“…A smoking ban without exceptions for the hospitality industry would be the most cost-effective measure to reduce cardiovascular morbidity and mortality [3,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…A smoking ban without exceptions for the hospitality industry would be the most cost-effective measure to reduce cardiovascular morbidity and mortality [3,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in mortality was only noted 3 years following the introduction of the legislation in the year 2007. Studies have shown that there is usually an immediate decline in mortality following smoking ban in public places [2][3][4][5][6][7][8][9][10][11] . The decrease in mortality in 2007 could be attributed to better enforcement of the smoking ban as evidenced by a marked increase in fines 13 and a decrease in the importation of cigarettes during that year 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking ban legislation has been shown to lead to an immediate and significant reduction in acute myocardial infarction (AMI) risk in a number of studies [2][3][4][5][6][7][8][9][10][11] . Furthermore, the community risk reduction brought about by smoking bans increases with time 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonuç olarak İESD'ye kronik maruziyet aterogenez ve akut koroner sendromu tetiklemektedir (120)(121)(122)(123) . Bununla birlikte yakın zamanda uygulanan sigara içme yasakları ile akut koroner sendrom nedeniyle acil başvurusu yaklaşık %17'lik bir azalma göstermiş-tir (124) . Temiz hava sahalarının oluşturulduğu bölge-lerde hem akut koroner sendrom nedeniyle hastane başvurularının hem de ambulans çağrılarının azaldı-ğı gösterilmiştir (116) .…”
Section: Kardiyovasküler Hastalıkunclassified